Fast crack bounds: estimativa de cota superior e solução numérica a evolução de trincas em modelos de tensão constante - Lara, Alexandre Guilherme de (2020)
Most components operate under alternated loading. Under these conditions, the static approach are insufficient describe the behavior, considering the the complexity of the fatigue phenomenon, with the need for other approaches, such as an Linear Elastic Fracture Mechanics (LEFM). LEFM has several models of evolution of cracks to describe the crack propagation in fatigue. The present work edscribes a new method of determination to the Upper Bound crack size, under Constant Loading Tension in one dimension. The Paris-Erdogan and Forman models were object of study . A simulation based on the approximate numerical solution was performed, and a convex combination of the upper and lower dimensions applied. Relative error for a numerical solution was measured by the fourth-order Runge-Kutta method, and the new method applied to the FCB model presented satisfatory results.